Effect of Taxation on Financial Performance of Small and Medium Enterprises in Kayunga: A Case of Kayunga Town Council - Charles Sokiri (Uganda Christian University, 2023)
The study examined the effect of taxation on financial performance of SMEs taking a case of Kayunga town council to establish the relation between taxation and financial performance that has been largely not been considered by the SMEs. It was guided by three research objectives; i) to find out the effect of tax rates on the financial performance of Small and Medium Enterprises in Kayunga town council; ii) to determine the effect of tax policies on the financial performance of Small and Medium Enterprises in Kayunga town council and iii) to examine the effect of tax reforms on financial performance of Small and Medium Enterprises in Kayunga town council Using a cross sectional design on a sample of 80 respondents, the study employed both self – Administered Questionnaires and interview guide and collected both Primary qualitative as well as quantitative data which was processed using SPSS Version (20). A descriptive research design was used with qualitative and quantitative research approaches. Registering a response rate of 70%, the results of Pearson‟s two tail statistic revealed that all the study variables rates , policies and reform respectively had a negative significant relationship with financial performance of SMEs in Kayunga town council with correlation coefficients of r= 0.793, p<0.01, r= 0.803, p<0.01) and (r= 0.686, p<0.01).Relatedly, regression analysis revealed that tax rates and tax reforms negatively affect financial performance with net contributions of 49.7% to 25.8% on financial performance of SMEs. The researcher concluded that on the overall, financial services accounts for 74.5.7% of the variation in financial performance of the SMEs at Kayunga town council and that whereas tax rates and reforms negatively affect financial performance, tax policies show the highest percentage. The research thus, recommends that since tax rates and policies have the biggest positive contribution to financial performance of SMEs, the SMEs players in the region with the impact of taxation on financial performance of SMEs in Kayunga Town council and increase the financial knowledge of the members that in return improves the capacity to make better decisions regarding finance of SMEs
This is a dissertation.